Implementasi Manajemen Kategori Dalam Manajemen Ritel Modern - Hesti Respatiningsih (FE Program Studi Manajemen, 2008)
A new paradigm in modern retail management is aplacement of retailer in a certain point/chain in the distributionpath/goods supply where the supplier is to be part of the wholeprocess for the available of the products from the top up to down.This paradigm demands the same perception between the supplierand retailer for the available needs and the satisfaction ofconsumers as the aim of the process. Category management isaccepted as the approach of handling products in category levelthrough structural systematic classification onassortment/products mix. The implementation of categorymanagement is in modern retail management such as: mixmargin, standard implantation/space management and privatelabeling.Keyword: Category management, product mix, mix margin,standard implantation, private labelling